The Determination of Body Defects, Hatching and Chick Quality Traits in Partridge (Alectoris Chukar) Parents - Selman Yıldırım; Mehmet Akif Boz; Kadir Erensoy (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the relationships between body defects, egg and chick quality and hatching results at different age periods of the laying period of partridges raised in production conditions (cage system). The study was based on three different periods. The first period is the pre-peak egg production period (˂200 eggs), the second period is the peak egg production period (˃200 eggs) and the third period is the post-peak egg production period (˂200 eggs). These periods also represent the age of the animals. As material, 432 female and 216 male partridges in their first egg production year were used. The study was organized according to the random plots experimental plan. There were changes in body defects and other health parameters depending on egg production periods. Foot-pad dermatitis and elbow burns increased with increasing age. Parent partridges had better head, neck, back, chest and tail feather condition before peak egg production. Egg weight increased with advancing age. Hatching egg characteristics such as excessively pointed eggs and eggs with calcium deposits decreased in the peak and post-peak yield period. Eggshell transparency increased with advancing age. Fertility was higher in the pre-peak egg yield period compared to other periods. Hatchability was lower after the peak period. Tona score of chicks decreased with age. There were weak negative and positive phenotypic correlations between many traits. Practices that prevent body injuries in the early egg production period and deteriorating feather condition with advancing age, decreasing shell opacity, deterioration in hatching performance and chick quality traits in partridges will be beneficial in terms of increasing both production performance and animal welfare.